Proceso de atención de enfermería en paciente con lupus eritematoso sistémico: un estudio de caso - Bastidas Buste , Andrea Carolina (2024)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of antibodies that attack organs and tissues. Globally, it was estimated that more than five million people suffered from some form of SLE, and in Ecuador, the prevalence was 40 cases per 100,000 inhabitants. Among its complications is osteonecrosis (ON), presenting itself as one of the most common and serious at the joint level, with an incidence in patients that ranges between 2.1% and 52%. For this reason, the purpose of the case study was to establish integrated and personalized nursing interventions in the patient with osteonecrosis in systemic lupus erythematosus, for the prevention of associated complications and the improvement of quality of life. Regarding the methodology, a retrospective evaluation and an approach based on Marjory Gordon's functional patterns was applied, determining alterations such as the cognitive-perceptual pattern, nutritional metabolic pattern, self-perception-self-concept pattern and health perception management pattern. Also, the Barthel index scale was used, which demonstrated a moderate degree of dependence in their daily activities 80/100. Thus, through nursing taxonomies, nursing care plans were proposed that integrated physical, behavioral and emotional aspects focused on addressing chronic pain, impaired tissue integrity, unbalanced nutrition: less than the body's requirements, hopelessness and ineffective self-management of the health. In this way, it is intended that comprehensive support be provided during the disease, providing continuous monitoring that mitigates the adverse effects associated with the chronic condition.